Higher operads, higher categories - Leinster, Tom (Cambridge University Press, 2004)
Category theory has experienced a resurgence in popularity recently because of new links with topology and mathematical physics. This book gives a user friendly account of higher order category theory and presents operads and multicategories as a natural language for its study. The author has included necessary background material and applications as well as appendices containing some of the more technical proofs that might have disrupted the flow of the text. This book should be a valuable resource to graduate students and researchers in the field.